2016
DOI: 10.1021/acsinfecdis.6b00167
|View full text |Cite
|
Sign up to set email alerts
|

Reviving Antibiotics: Efflux Pump Inhibitors That Interact with AcrA, a Membrane Fusion Protein of the AcrAB-TolC Multidrug Efflux Pump

Abstract: Antibiotic resistance is a major threat to human welfare. Inhibitors of multidrug efflux pumps (EPIs) are promising alternative therapeutics that could revive activities of antibiotics and reduce bacterial virulence. Identification of new druggable sites for inhibition is critical for the development of effective EPIs, especially in light of constantly emerging resistance. Here, we describe EPIs that interact with periplasmic membrane fusion proteins, critical components of efflux pumps that are responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 40 publications
3
137
0
Order By: Relevance
“…The AcrAB-TolC pump that belongs to the RND family is the main efflux pump in E. coli clinical isolates (10). This pump is composed of an inner membrane transporter AcrB, periplasmic membrane fusion protein AcrA, and an outer membrane channel TolC (11).…”
Section: Introductionmentioning
confidence: 99%
“…The AcrAB-TolC pump that belongs to the RND family is the main efflux pump in E. coli clinical isolates (10). This pump is composed of an inner membrane transporter AcrB, periplasmic membrane fusion protein AcrA, and an outer membrane channel TolC (11).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds having an MIC ≤100 μM in combination with novobiocin were then evaluated in a checkerboard assay to determine the minimum potentiation concentration (MPC) that results in a fourfold improvement (MPC 4 ) in the MIC of novobiocin. 20 Compounds with an MPC 4 Nov ≤ 50 μM were examined for their affinity as substrates for the AcrAB-TolC efflux pump and also their ability to permeate the OM barrier. To accomplish this, compounds were tested in two additional cell-based bacterial growth inhibition assays.…”
Section: Resultsmentioning
confidence: 99%
“…20,22 The SPR assay was validated using both negative and positive controls, as described previously. 20 The HT uptake assay was performed in a temperature-controlled micro-plate reader (Tecan Spark 10M) equipped with a sample injector, in fluorescence mode. Data were fitted to extract initial rates, as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, macrolides were believed to block the passage of all peptides through the PET when they are 2–5 amino acids long. However, recent studies have shown that several proteins with specific N‐terminal sequences can still be synthesized even when a macrolide is bound to the ribosome and that protein synthesis can become interrupted at any stage in response to specific stalling motifs . The role of this selective protein inhibition in macrolide activity is presently unclear.…”
Section: Introductionmentioning
confidence: 99%